Sosialisasi dan Pelatihan (Stunting dan Konseling PMBA) Kader Pembina Posyandu Desa Kuripan Utara - Wiwin Lastyana; Baiq Fitria Rahmiati; Wayan Canny Naktiany; Junendri Ardian; M. Thonthowi Jauhari (LPPM Universitas Bumigora, 2022)
Stunting is a serious public health problem and its prevalence remains high, especially in developing countries. Stunting is caused by a lack of nutritional intake for a long time in the first 1000 days of life, which is a critical period. Posyandu is a form of Community Based Health effort (UKBM) carried out by, from, and with the community, to empower and provide convenience for the community to obtain health services for mothers, infants, and toddlers. This community service activity aims to improve the knowledge and skills of cadres in preventing stunting and in Baby and Child Feeding counseling. This activity was carried out on February 21, 2022. The activity lasted for 3 hours and the participants who attended the training were 40 training cadres located in the Kuripan Utara Village Office Hall. The participants were very enthusiastic about participating in every material given in the training. The cadres of the training participants received clarification on various questions regarding nutrition that had been developing with an inaccurate understanding. Participants also became more aware of Baby and Child Feeding toddlers and could do counseling.